Psychosocial and economic impacts on olympic/paralympic athletes and coaches in aquatic sports due to COVID-19: perceptions, discourses and perspectives - Bettine, Marco (2020)
This article seeks to present the perspective of 15 protagonists of the Brazilian Olympic and Paralympic movement on the way they are facing “Social Isolation” due to COVID-19, as the postponement of all sports competitions in the year 2020, being the most important of them the Tokyo 2020 Olympic and Paralympic Games. The objective of this work was to investigate the point of view of the 15 Olympic and Paralympic athletes and coaches of the aquatic modalities who trained in São Paulo on several factors of social isolation, such as training, anxiety, perspectives. This is a qualitative research, with virtual data collection and semi-structured interviews. Discussions: Postponement of the Games; Athlete Scholarship; Training. Considerations: Importance of Bolsa Atleta at this time of pandemic due to reduced wages and suspension of contracts with sponsors; Difference of Discourse between the collective subject athlete and trainer on the impacts of COVID in training; Political positioning against actions of the federal government, mainly the President of the Republic Jair Bolsonaro.